Collaborative Networked Organizations A research agenda for emerging business models - Camarinha-Matos, Luis M.; Afsarmanesh, Hamideh. (Springer US, 2004)
A research agenda for collaborative networks Purpose. Many practical application experiments and pilot cases nowadays provide evidence on what works and what still remains as a challenge for collaborative networked organizations (CNOs). The fast evolution of the information and communication technologies and in particular the so-called Internet technologies, also represents an important motivator for the emergence of new forms of collaboration. However, most efforts in this area are highly fragmented, considering only some partial facets and not a holistic perspective that would be required. We are therefore at a point in which it is necessary to define much more consolidated and sustainable research strategies for a second phase of research and development in this area. This book addresses the main disciplines involved in CNOs. It further synthesizes the views and opinions expressed by a large number of visionaries from the main disciplines involved in CNOs, and offers a comprehensive set of recommendations for the establishment of a research agenda on collaborative networks. As recognized experts in their specific areas, different authors in this book have presented work that is backed by a large number of research results, each focusing on specific facets of collaborative networks, and coming out of a large number of international and national projects.